If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9k + -6 + -3(2 + -5k) = 0 9k + -6 + (2 * -3 + -5k * -3) = 0 9k + -6 + (-6 + 15k) = 0 Reorder the terms: -6 + -6 + 9k + 15k = 0 Combine like terms: -6 + -6 = -12 -12 + 9k + 15k = 0 Combine like terms: 9k + 15k = 24k -12 + 24k = 0 Solving -12 + 24k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 24k = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 24k = 0 + 12 24k = 0 + 12 Combine like terms: 0 + 12 = 12 24k = 12 Divide each side by '24'. k = 0.5 Simplifying k = 0.5
| 3x^2+7x-41=0 | | 14.95+.13x=-15+.39 | | 6x+67=12x-5 | | k^2-k-56=0 | | 75/(-5)(-3)/.50(6) | | 14.95-.13x=-15+.39 | | 2e-x=1 | | 5+12x=16+x | | 2(5+x)-12=4 | | n^2-n-2=0 | | 5x-x=-10.4-2 | | k(3k+1)=0 | | (p+5)(p-1)=0 | | 2y+3y+8=-6 | | 2a+2f=134 | | z^2+2z= | | 1000=200+50x | | 9x=3(x-8) | | 5(3+4x)-6(7x-5)=2x-1 | | 2LogmM+logN-5logP= | | 13200-450x=13200-250x | | 49.75=20*2+.15m | | 7(2x+1)-6(x+8)=12 | | 24-10x+x^2=10x-x^2 | | LogA+lobB-logC+logD-logE= | | 7(2x+1)-6(x-5)=2x-12 | | x^3-64x-14=0 | | 7(2x+1)-6(x-5)=2x-1 | | 250=70+20b | | 2=4-2u | | 7(2x+1)-6(7x-5)=2x-1 | | 13200-450x=10560 |